(untitled) (Undergraduate Conference on Applied Linguistics, Linguistics, and Literature, 2022)
Learning speaking skills in English designed using video media, and the material presented is useful, will motivate learning. The purpose of this research is to; (1) knowing the process of implementing speaking skills of class VIII students at SMPN 2 Kendal in learning English using teaching videos, (2) describing speaking skills of class VIII students at SMPN 2 Kendal after learning English using teaching videos. Research methods; qualitative approach. The role of the researcher in this qualitative research is as a planner, data collector, analyzer, and as the originator of the research. This research using qualitative approach as descriptive research. The data and information are generated in the form of word. Results: (1) The process of learning English in Class 8A using teaching videos, went very well. The use of YouTube-based teaching videos can not only improve the skills of students but also foster students’ enthusiasm and activeness in learning. Video media is used to make it easier for students to learn KD 4.3.2 material. The use of teaching videos in the English learning process greatly influences the achievement of students’ speaking skills, (2) the achievement of speaking skills of grade 8A students of 69.7% fulfills the criteria for success, with details; 1 student achieved a very good predicate score (94-100), as many as 10 students had a good predicate (87-93), a total of 11 students predicated sufficient scores (80-86), and 10 students were still lacking or under the minimum completeness criteria.